Functional Capacity COVID-19 Survival Among Workers in Koja Public Health Center - Melinda Harini; Ira Mistivani; Widjajalaksmi Kusumaningsih; Peggy Sunarjo; Budiati Laksmitasari; Nelfidayani; Rizky Kusuma Wardhani; Ni Luh Made M J; Ratna Ekawati; Edvina; Prisca Ockta; Adhitya; Reni Rozanti; Ricky Fakhrazi; Felix Leo; Novita Suprapto Wati; Endang Sri Wahyuningsih; Dwi Oktavia; Rofi Yuliandra; Vinnaria Astuty; Sri Puji Wahyuni; Julieta Tantri; Gilang Rama Putra (Medica Hospitalia : Journal of Clinical Medicine, 2024)
Introduction: Coronavirus disease 19 (COVID-19) primarily affects the respiratory system and other organ systems which limit respiratory and physical status. The aim of this study is to evaluate functional capacity COVID-19 survivor among workers in Koja Public Health Center Methods: participant were enrolled on March-April 2022. Demographics, symptoms, functional scale post COVID-19 questionnaire, risk stratification, and 6-min walk test (6mwt) were analysed. Patients unable to walk were excluded from the study. Results: 79 participants, 38% was a health care worker, had a median age 33 (21-57) years and 43 women (54.4%). Men had higher 6mwt 518.2 (120-625.8) meter while women had 457 (340-600) meter p (<0.001), VO2max 17.47 (9.74-20.67) in men and 16.45 (14.07-19.19) in women p (<0.001), and METs 5.02 (2.78-5.90) in men and 4.69 (4.02-5.48) in women p (<0.001). Most of the participant had good fitness, 10 participant (12.7%) had functional limitation; 2 participants (2.5%) still had symptom. Conclusion: Despite being COVID-19 survivors, the workers at the Koja Public Health Center have good functional capacity.